Hospital Care for Newborn Babies: Quality Assessment, A Systematic Review - Jabbari, Hossein (Iran J Pediatr, 2015)
CONTEXT: Neonatal mortality rate is declining globally. The aim of the present study is to identify relevant indicators for assessing newborn care in hospitals by a systematic review. EVIDENCE ACQUISITION: A search on electronic data base and manual searches of personal files for studies on quality indicators of newborn care were carried out. Searching 9 bibliographic databases, we found 85 articles of which 22 exactly related ones were selected and studied. Hand search yielded 1 record were also searched and 2 records were included. RESULTS: A list of 87 structure, process and outcome indicators was formulated from the articles. Also 26 excess measures were identified in gray literature. After removing duplicates, and categorizing in 3 domains, 18 measures were input, 41 process and 34 outcome measures. CONCLUSIONS: These 93 indicators provide a framework for assessing how well the hospitals are providing neonatal care. These measures should be discussed in each context expert panels to address nationally applicable indices of neonatal care and may be adapted for local health settings.